Tomorrow’s HR management : (John Wiley, 1997)
In the future, will human resource management emerge as an even more critical factor in developing and maintaining a company's competitive edge, or will it become just one more outsourced function overseen by managers busy juggling several other responsibilities at the same time? Will HR departments buckle under the constant pressure to do more with less, or will inspired leaders develop practices that link HR to overall business strategies and improved organizational capabilities? Tomorrow's HR Management is about creating the future right in your own company—adapting to meet the needs of your enterprise and the demands of a changing business environment.